The potential vegetable dietary of Plio-Pleistocene Hominids at Makapansgat - Maguire, Brian (Bernard Price Institute for Palaeontological Research, 1980)
Neither fossil pollens nor macroscopic plant remains have as yet been reported from the Makapansgat Limeworks breccias; hence there exists no direct means of assessing the character of the local floral environment during australopithecine times. However, it is suggested that provided acceptable evidence on the nature of the contemporaneous climate and particularly rainfall can be obtained, by indirect means a comparatively full picture may be presented, both of the local vegetation and of the plant foods available to hominids in the area at that time. The methods and types of data employed in deducing the nature of the palaeoflora at Makapansgat, under hypothetical conditions of rainfall both higher and lower than the present, are briefly summarised. The extant vegetation in the Makapansgat area is briefly described and the food plant component is discussed with reference to the numbers and types of food plant present, the numbers and types of foods these plants provide and the times at which they are availabe. These data relate to two study areas, one lying within an 8 km radius of the Limeworks site, the other lying within a 16 km radius. The present climate and floral-climatic relationships at Makapansgat in recent and historic times are discussed. The nature of secondary disturbance in the area is discussed and its effects emphasised. The conjectured nature and food plant component of the prehistoric Makapansgat vegetation is discussed in relation to hypothetical conditions of both increased and diminished rainfall. The five vegetation types represented at Makapansgat provide a total of 117 food plants within a radius of 8 km of the Limeworks site, and 150 within a 16 km radius. These plants are mainly trees and shrubs providing edible fruits.
Main article
Keywords: vegetation; Makapansgat; breccia; Limeworks